Fluorescence spectroscopy analysis of fly ash removal from aqueous systems: adsorption of alginate to silica and alumina. Issue 30 (21st July 2022) - Eltaboni, Fateh; Singh, Sehaj; Swanson, Linda; Swift, Thomas; Almalki, Abdulraheem SA
Abstract : We study the adsorption processes of alginate for the removal of fly ash (a toxic industrial waste, mainly consisting of silica and alumina particles, commonly found discharged into the environment.) Abstract : Fly ash is a toxic industrial waste, mainly consisting of silica and alumina particles, that has been found discharged into the environment. It is proposed that alginate, a naturally occurring biopolymer, can bind to these minerals and thus play a role in water purification. The binding forces involved in this process consist of weak interactions, such as van der Waals forces and electrostatic interactions. Although the attachment of alginate to mineral surfaces is mainly governed by its carboxylate groups, hydroxyl moieties could play a role in the interaction between the polymer and minerals. This work aims to use the SiO2 and Al2 O3 particles as models for fly ash and to show the use of alginate biopolymers (fluorescently labelled with an aminonaphthaline sulfonate fluorophore (AmNS)) to coagulate them. The addition of simple electrolytes like NaCl and CaCl2 encourages the coiling of the polymer chain at high pH values which has an effect on its capability to bind to the inorganic particles. A combination of fluorescence and ICP-MS demonstrated that alginate has a considerable adsorption affinity for Al2 O3, whereas it attracts SiO2 weakly. The adsorption process is pH dependent: strong adsorption was observed at low pH values. The dependence of adsorption on the mineral (Al2 O3 and SiO2 ) concentration was also examined under different pH conditions: the adsorption amount was observed to increase by increasing the solid concentration. Adsorption isotherms obtained at low and high mineral concentrations were found to be Henry in type.